Body scan meditation enhances the autonomous sensory meridian response to auditory stimuli. (June 2022) - Glim, Sarah; Braun, Lynn; Hayd, Sophie; Kuenz, Amelie; Rosak, Felicitas; vom Bruch, Jule
Autonomous sensory meridian response (ASMR) is a pleasant, tingling sensation on the skin that can be elicited by certain auditory and visual stimuli, with the intertwining of sensory modalities and emotional reactions observable in this phenomenon resembling that of synesthesia. The current study shows that the perception of ASMR-associated tingles can be enhanced by means of a prior mindfulness exercise in which attention is drawn to the body. This finding contributes to a better understanding of the crossmodal mechanisms behind ASMR and emphasizes the role that attentional processes play in its unfolding.